Empowering Village Paralegals through Local Wisdom: A Model for Rural Legal Aid - Ummi Maskanah; Nia Kania Winayanti; Rishki Yuky Restu; Siti Pujiastuti Suhartini (Golden Ratio of Law and Social Policy Review, 2026)
This study aims to develop a village-based legal aid service model through the empowerment of village paralegals based on local wisdom as a strategy to improve access to justice for rural communities. This study uses normative legal research with statutory, conceptual, and comparative approaches. The legal materials consist of statutory regulations, court decisions, policy documents, and academic literature obtained through library research. The analysis is conducted through doctrinal analysis, regulatory interpretation, and deductive reasoning. The findings show that village-based legal aid can bring legal services closer to rural communities that often face geographical, economic, institutional, and informational barriers. The proposed model consists of three main pillars: local wisdom-based paralegal training, technology-supported legal aid services, and sustainable funding mechanisms involving village governments, legal aid organisations, local governments, and community stakeholders. Village paralegals may provide legal education, initial consultation, case documentation, mediation support, community assistance, and referrals to authorised legal aid providers. However, their litigation-related role must be limited to assisting advocates or legal aid providers under proper supervision, not independent court representation. The study also identifies several implementation challenges, including low public legal awareness, limited funding, insufficient training, weak institutional coordination, and limited public recognition of paralegals. Therefore, strengthening village legal aid posts, improving paralegal training and supervision, utilising digital platforms, and establishing sustainable funding and referral mechanisms are necessary to ensure effective and equitable legal aid services in villages.